Outcome in patients undergoing postponed elective surgery during the COVID-19 pandemic (TRACE II): study protocol for a multicentre prospective observational study. Issue 6 (22nd June 2022) - Werger, Alice C; Breel, Jennifer; van Kuijk, Sander; Bulte, Carolien S E; Koopman, Seppe; Scheffer, Gert Jan; Noordzij, Peter G; in 't Veld, Bas A; Wensing, Carin G C L; Hollmann, Markus W; Buhre, Wolfgang; de Korte-de Boer, Dianne
Abstract : Introduction: During the COVID-19 pandemic many non-acute elective surgeries were cancelled or postponed around the world. This has created an opportunity to study the effect of delayed surgery on health conditions prior to surgery and postsurgical outcomes in patients with postponed elective surgery. The control group of the Routine Postsurgical Anesthesia Visit to Improve Patient Outcome (TRACE I) study, conducted between 2016 and 2019, will serve as a control cohort. Methods and analysis: TRACE II is an observational, multicentre, prospective cohort study among surgical patients with postponed surgery due to COVID-19 in academic and non-academic hospitals in the Netherlands. We aim to include 2500 adult patients. The primary outcome will be the 30-day incidence of major postoperative complications. Secondary outcome measures include the 30-day incidence of minor postoperative complications, 1 year mortality, length of stay (in hospital, medium care and intensive care), quality of recovery 30 days after surgery and postoperative quality of life up to 1 year following surgery. Multivariable logistic mixed-effects regression analysis with a random intercept for hospital will be used to test group differences on the primary outcome. Ethics and dissemination: Ethical approval was obtained from the Institutional Review Board of Maastricht University Medical Centre+ and Amsterdam UMC. Findings will be presented at national and international conferences, as well as published in peer-reviewed scientific journals, with a preference for open access journals. Data will be made publicly available after publication of the main results. Trial registration number: NL8841.